Malpura: A mutton breed of sheep needs to be conserved - KUMAR, ARUN; SINGH, UMESH; KUMAR, SUSHIL; SHARMA, R C; ARORA, A L (The Indian Journal of Animal Sciences, 2011)
Malpura is one of the important sheep breeds among 8 breeds available in Rajasthan. This breed derives its name from the small town “Malpura” of Tonk districts, of Rajasthan and predominates in Jaipur, Tonk, Swai madhopur, Ajmer, Chittorgarh and Bhilwara districts of Rajasthan. Ewes of this breed have good mothering ability and are having sufficient milk to sustain and accelerate the growth of their neonates. Lambs of this breed are quite suitable for fat lamb production. The animals are fairly well built and face is of light brown colour with short and tubular ears. The fleece is white and extremely coarse. Malpura is a medium to heavy size breed, and on an average its adult body weight is 40 kg in males and 30 kg in females. In farmers’ flocks birth weight ranged from 2.77 to 3.50 kg and 6 month body weight ranged from 16.4 to 18.94 kg. At organized farm average birth weight ranged from 2.64±0.012 to 3.07±0.02 kg, 3– month weight ranged from 10.4±0.07 to 14.60±0.11 kg, 6–month weight ranged from 14.0±0.11 to 21.00±0.15 kg and 12 month weight ranged from 21.4±0.20 to 27.63±0.25 kg. The average age at first service, weight at first service, age at first lambing, weight at first lambing and lambing interval were 650 days, 27 kg, 810 days, 28 kg and 370 days respectively. Average lambing percentage, twin lambing, litters size at birth and weaning was 90%, 2.55%, 1.02 and 0.97 respectively. Dressing per cent on live weight and empty live weight basis were 50.66±0.71 and 59.12±0.72%. Average first greasy fleece yield (GFY), adult GFY and annual GFY in Malpura female under field conditions were 511.25, 360.28 and 1085.91 g, respectively. In 3 clips, the annual fleece yields of Malapura rams and ewes in farmer’s flocks were 1.52 and 1.12 kg respectively. The wool produced from the Malpura sheep is around 40 micron in diameter with around 75% modulation. Staple length of 6 month grown fleece is around 5 cm. The lactation milk yield of Malpura varied from 21.36 to 64.50 kg and the average milk yield per day/ewe varied between 0.366 kg and 0.748 kg.